2014
DOI: 10.3109/02699052.2014.915987
|View full text |Cite
|
Sign up to set email alerts
|

Acute and longitudinal changes in motor cortex function following mild traumatic brain injury

Abstract: mTBI appeared to have little effect on cortical excitability, but an acute and long-lasting effect on intra-cortical inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
60
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 36 publications
7
60
0
2
Order By: Relevance
“…TBI may vary in severity, but Ͼ75% of all TBI is classified as mild Elder and Cristian 2009;Langlois et al 2005;Miniño et al 2006). In this study, we sought to determine how rmTBI affects the pediatric brain.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…TBI may vary in severity, but Ͼ75% of all TBI is classified as mild Elder and Cristian 2009;Langlois et al 2005;Miniño et al 2006). In this study, we sought to determine how rmTBI affects the pediatric brain.…”
Section: Discussionmentioning
confidence: 98%
“…In humans, the use of transcranial magnetic stimulation from 72 h to 2 mo after mTBI has shown increases in intracortical inhibition (Miller et al 2014). Young athletes who have sustained multiple concussions have also been reported to have abnormal intracortical inhibition (De Beaumont et al 2007, 2011Tremblay et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMS has been used extensively in the investigation of neurological disorders such as stroke, Parkinson's disease and multiple sclerosis 10 , as well as those with long-term cognitive and motor impairments with concussion sustained in early adulthood. 11,12 Specifically brain injury, Christyakov et al 13 and Miller et al 14 showed increased intracortical inhibition in mild to severe TBI patients two weeks following injury. Similarly, De Beaumont et al 9 showed increased intracortical inhibition in previously concussed collegiate athletes with repeated concussions.…”
Section: Introductionmentioning
confidence: 99%
“…Static comparisons of the inhibitory marker short-interval intracortical inhibition (SICI), a GABA A mediated form of inhibition, have largely failed to differentiate between concussion and control groups at the acute (Bashir et al, 2012; Powers et al, 2014; Pearce et al, 2015) and chronic (De Beaumont et al, 2007, 2009; Tremblay et al, 2011) stages post-injury, however, there has been a report of reduced SICI in retired Australian football players (Pearce et al, 2014). Of all the TMS measures of motor cortex excitability, the most consistent finding in concussed individuals is an enhanced cortical silent period duration, a GABA B mediated form of intracortical inhibition (Tremblay et al, 2011; De Beaumont et al, 2012; Miller et al, 2014; Pearce et al, 2014, 2015) that appears to persist (De Beaumont et al, 2007) or is even enhanced (De Beaumont et al, 2009) as time from injury increases. However, even though cortical silent period is enhanced in younger active Australian football players with a history of concussion (Pearce et al, 2015) in a cohort of older retired players the silent period was decreased (Pearce et al, 2014).…”
Section: Introductionmentioning
confidence: 99%